2010
DOI: 10.1194/jlr.d007328
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF/MS analysis of archaebacterial lipids in lyophilized membranes dry-mixed with 9-aminoacridine

Abstract: This article is available online at http://www.jlr.org erophospholipids, allowing a rapid, sensitive, and highly informative approach for the direct analysis of cell lipid extracts ( 2 ). Notably the use of the novel matrix 9-aminoacridine in MALDI-TOF/MS enables the fast and reliable detection of anionic phospholipids and also cardiolipin species ( 2 ).In our study we extended the use of 9-aminoacridine as a matrix for the MALDI-TOF/MS to glycerolipids and glycerophospholipids of extremely halophilic microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…It has been shown that this emerging analytical technique can be used to directly acquire lipid profi les of biological samples, thus skipping extraction and separation steps (30)(31)(32)(33). We successfully adopted this experimental approach to describe the lipid composition of bacterial and mitochondrial membranes ( 30,31,33 ) and to detect lipid markers in blood serum ( 32 ). Importantly, we found that the phosphatidylcholine-tolysophosphatidylcholine ratio could be easily determined by MALDI-TOF/MS analyses of native blood serum and followed as a clinical parameter in various diseases ( 32 ).…”
Section: Maldi-tof/msmentioning
confidence: 99%
“…It has been shown that this emerging analytical technique can be used to directly acquire lipid profi les of biological samples, thus skipping extraction and separation steps (30)(31)(32)(33). We successfully adopted this experimental approach to describe the lipid composition of bacterial and mitochondrial membranes ( 30,31,33 ) and to detect lipid markers in blood serum ( 32 ). Importantly, we found that the phosphatidylcholine-tolysophosphatidylcholine ratio could be easily determined by MALDI-TOF/MS analyses of native blood serum and followed as a clinical parameter in various diseases ( 32 ).…”
Section: Maldi-tof/msmentioning
confidence: 99%
“…Lipid bands on the TLC plate were visualized using ninhydrin for amino lipids and either 30 % H 2 SO 4 or iodine vapour for all lipids. Some lipids visualized using iodine vapour were scraped and analysed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS, AXIMA Resonance, Shimadzu) according to the procedure of Angelini et al (2010). Cells of M. thermautotrophicus DSM 1053 T at the late exponential phase were also examined as a reference.…”
mentioning
confidence: 99%
“…In addition, while two cardiolipin analogs are present in the lipid pattern of standard PM (34,47), no cardiolipins have been found in claret membranes. While both cardiolipin analogs were found to be enriched in bacteriorhodopsin chromatographic bands of H. salinarum (34), only small amounts of BPG were detected among residual phospholipids associated with solubilized Bop I of Haloquadratum .…”
Section: Discussionmentioning
confidence: 99%